Avaliação do potencial do fungo Kretzschmaria zonata para produção de enzimas hidrolíticas e caracterização de xilanase para produção de xilooligossacarídeos - Morales, Marciana da Luz (2020)
The xylanase enzyme (EC 3.2.1.8) is responsible for catalysing the hydrolysis of xylosidic bonds in the xylan chain to produce xyloligosaccharides, which are converted to xylose by β xylosidases (EC3.2.1.37). Xylanases are widely used in different areas of food industry, such as baking, juice clarification, production of the prebiotics xyloligosaccharides and xylitol sweetener. Fungi are very used for xylanases production, mainly because they secrete large amounts of enzymes. The aim of this work was to perform the enzymatic prospecting of the fungus Kretzschmaria zonata, using different carbon sources in semi-solid fermentation system, to partially purify and to characterize a xylanase, and to apply this enzyme in the production of xyloligosaccharides. The fungus K. zonata was isolated from sick roots and trunks of teak (Tectona grandis) and kept in malt agar extract plates. For enzyme production, different agroindustrial residues were used as carbon sources and inducers of enzymatic production, namely: corncob, wheat bran, soybean hull, teak heartwood, elephant grass and green coffee husk. The activities of xylanase, FPase, endoglucanase, mannanase, pectinase, βglucosidase, β-xylosidase, β manosidase, α-galactosidase, α-arabinofuranosidase, βcellobiohydrolase and laccase were determined. The partial purification of the xylanase secreted by the fungus K. zonata was performed in two steps using liquid chromatography, first using a Q-Sepharose anion exchange column at pH 5.0, and secondly using the same column, but at pH 7.0. Evaluation of enzyme purity was performed by electrophoresis gel and xylanolytic activity confirmed by zymogram. Xylanase was biochemically characterized and applied for xyloligossacarides production using 2 % Beechwood xylan, and the hydrolysis products were revealed by thin layer cromatography. K. zonata. produced different enzymes when cultivated under the tested carbon sources and corncob was the residue that best induced the xylanase activity. The crude extract of the fungus grown on corn cob was subjected to the first purification step in liquid chromatography. At this stage, it was possible to detect three peaks with xylanase activity. The first and largest peak was eluted before the saline gradient, which characterizes positively charged enzyme(s). The fraction containing the highest activity peak was subjected to a new Q-Sepharose column chromatography at pH 7.0. With the analysis of the electrophoresis gel, it was observed that these two steps were not sufficient for total purification of the enzyme, since more than one protein band were visualized in the gel. The partially purified K. zonata xylanase showed higher activity at pH 5.0 and 50 °C, being stable at pH values from 4 to 8. It was poorly thermostable at 50 and 60 °C, since it maintained only 40 % of relative activity after 30 minutes of incubation; at 70 ° C it maintained 30 % of activity for the same incubation period. The xylanase maintained 88, 91 and 95 % of relative activity, respectively, in the presence of CaCl2, MnCl2 and ZnCl2, at 5 mM concentration, and the enzyme was lightly activated in the presence of NaCl, presenting 109 % of activity. It was inhibited in the presence of CuSO4 and sodium dodecyl sulphate. The partially purified xylanase showed higher affinity for Beechwood xylan as substrate and it also showed activity against cellulosic substrates. This xylanase was able to hydrolyze Beechwood xylan at a concentration of 2 %, showing as main hydrolysis products xylobiose and xilotriose, which have potential for applications in the food industry as prebiotics. This xylanase proved to be a promising alternative for application in the production of xyloligosaccharides, and this is the first work that describes xylanases produced by the fungus K. zonata.